Temporality of perception during the consumption of French grape brandies with different aging times in relation with aroma compound release. (28th July 2015) - Fiches, Guillaume; Saint Eve, Anne; Jourdren, Solenne; Déléris, Isabelle; Brunerie, Pascal; Souchon, Isabelle
Abstract: Distilled beverages are appreciated by consumers for their aromatic richness and changes during product consumption, but mechanisms still remain unclear. In this context, the objective of the present study was to better understand the origin of temporal perception by a combined approach (dynamic sensory and instrumental) during the consumption of brandies with different aging and known to have different qualities. The five brandies were significantly perceived differently according to sensory profile results. Temporal sensory results showed common perception sequences between products in terms of taste and trigeminal sensations whereas different aromatic sequences were highlighted between products after they were spat out, depending mainly on their aging. Releases over consumption of some aroma compounds specific of brandy flavour were measured in panelist's nose by proton transfer reaction‐mass spectrometry. In all cases, similar release patterns were observed, although higher intensities were observed for esters in aged brandies, where they were at higher levels. It is therefore proposed that quantitative differences and not specific release patterns are at the origin of the observed pattern of temporal dominance of sensations. Aroma compounds from wood could also be possible at the origin of aromatic interactions with other perceptions, changing brandy overall perception. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This work aimed at understanding the changes in perception during the consumption of French grape brandies with different aging times.